Fundamentals of Labor Economics, 3rd Edition - Thomas Hyclak; Geraint Johnes (Cengage Learning, 2020)
Examine the essential aspects of modern labor economics from an international perspective with Hyclak/Johnes/Thornton's highly accessible FUNDAMENTALS OF LABOR ECONOMICS, 3E. This timely edition provides a comprehensive survey of economic theory and empirical evidence on purely competitive labor markets. Using their diverse professional experience, the authors examine the impact of imperfect competition, incomplete information and uncertainty, and institutional factors -- stemming from government regulation, unions, social norms, and human resource management policies -- on wages and employment opportunities. The latest updates address important issues today, such as wage and income inequality, labor market effects of international migration, the impact of occupational licensing on wages and employment, and labor aspects of the current ""gig"" economy. Extensive research and cases give you a better understanding of the world in which you work and manage others for ongoing professional success. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.